2017
DOI: 10.1071/py16145
|View full text |Cite
|
Sign up to set email alerts
|

Understanding practitioner professionalism in Aboriginal and Torres Strait Islander health: lessons from student and registrar placements at an urban Aboriginal and Torres Strait Islander primary healthcare service

Abstract: Aboriginal and Torres Strait Islander peoples continue to be pathologised in medical curriculum, leaving graduates feeling unequipped to effectively work cross-culturally. These factors create barriers to culturally safe health care for Aboriginal and Torres Strait Islander peoples. In this pilot pre-post study, the learning experiences of seven medical students and four medical registrars undertaking clinical placements at an urban Aboriginal and Torres Strait Islander primary healthcare service in 2014 were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(14 citation statements)
references
References 14 publications
0
14
0
Order By: Relevance
“…Aboriginal community‐controlled health services have proven to provide more equitable, higher‐quality care to Indigenous Australians 6 . It would also provide opportunity to establish meaningful patient‐provider relationships that challenges any pre‐conceived biases or assumptions, both conscious and unconscious, about Aboriginal and Torres Strait Islander people 48 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Aboriginal community‐controlled health services have proven to provide more equitable, higher‐quality care to Indigenous Australians 6 . It would also provide opportunity to establish meaningful patient‐provider relationships that challenges any pre‐conceived biases or assumptions, both conscious and unconscious, about Aboriginal and Torres Strait Islander people 48 …”
Section: Discussionmentioning
confidence: 99%
“…6 It would also provide opportunity to establish meaningful patient-provider relationships that challenges any preconceived biases or assumptions, both conscious and unconscious, about Aboriginal and Torres Strait Islander people. 48 Individual physicians are not inherently at fault for their implicit bias, nor should blame be placed against individuals. However, physicians do have a responsibility to be aware of and actively engaged in efforts to reduce racial disparities in healthcare.…”
Section: Addressing Implicit Bias and Racial Disparitiesmentioning
confidence: 99%
“…In light of this ongoing struggle there is increasing recognition within the health community to advance and enable best practice care provision for Aboriginal peoples [7,8]. This is on a background of international evidence demonstrating a lower quality of healthcare provision for ethnic and minority groups across the globe [9].…”
Section: Daily Demonstrations Of Solidarity Survivorship and Resiliementioning
confidence: 99%
“…This is in recognition of the importance of place-based care; health care that is considerate of the local priorities, expectations and ways of being of the community served. [7] A focus on literature detailing knowledges from Central Australia, South Australia and North Western Australia guide the following domain considerations.…”
Section: Style Of Communication and The Mode Approach And Timing Of mentioning
confidence: 99%
“…Four principles of medical professionalism in the context of care for Aboriginal and Torres Strait Islander people were identified from a study of the learning experiences of medical students and registrars by Askew et al (2017). Despite being a requirement for Australian health services, Kwedza et al (2017) found that clinical governance is poorly understood by people working in rural and remote primary care.…”
mentioning
confidence: 99%